2000
DOI: 10.2337/diabetes.49.12.1986
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus-mediated gene transfer into pancreatic islet cells.

Abstract: Baculovirus transduction is a gene transfer method that uses a moth cell virus for mammalian cells in culture, which results in a high-level prolonged expression. Here we demonstrate that recombinant baculoviruses can serve as efficient gene transfer vehicles for delivering foreign genes driven by mammalian promoters into human and mouse pancreatic islet cells. Existing methods, such as various transfection and electroporation techniques, either suffer from low efficiency or cause extensive membrane damage. Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Previously, it has been shown that they possess the capacity to transduce a variety of mammalian cell types including mesenchymal cells, neural glial cells and hepatocytes. [1][2][3][4][14][15][16][17] Our results show that baculoviruses are able to transduce brain cells efficiently in vivo and possess a very specific cell tropism in rat brain. The choroid plexus epithelial cells were transduced with high efficiency (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that they possess the capacity to transduce a variety of mammalian cell types including mesenchymal cells, neural glial cells and hepatocytes. [1][2][3][4][14][15][16][17] Our results show that baculoviruses are able to transduce brain cells efficiently in vivo and possess a very specific cell tropism in rat brain. The choroid plexus epithelial cells were transduced with high efficiency (Figure 1, Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…So far, baculovirus vectors have been shown to transduce various dividing and nondividing mammalian cell lines in vitro (1,8,12,20,29,42,48,49,52). Baculovirus-mediated gene transfer has also been successful in vivo (1,21,23,24,27,42,47,48,50).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected at 1.3-1.7 Hz because most vesicle fusion events appeared to last several seconds. Cells and islets were superfused with Krebs-Ringer buffer containing 119 mM NaCl, 4.7 mM KCl, 25 mM NaHCO 3 , 2.5 mM CaCl 2 , 1.2 mM MgSO 4 , 1.2 mM KH 2 PO 4 , and 25 mM glucose (MIN6 cells) or 11 mM (beta cells or islets) (17). All imaging experiments were conducted at 35-37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Islet cells were dissociated by using 0.25 mg͞ml trypsin. Cells or islets were cultured on glass coverslips and incubated in RPMI medium 1640 containing 11.5 mM glucose, 10% FBS, 100 units͞ml penicillin, and 100 g͞ml streptomycin at 37°C for 1-2 days before transduction (17). MIN6 cells (18) were grown in DMEM (Life Technologies) containing 25 mM glucose, 10% FBS, 100 units͞ml penicillin, and 100 g͞ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%